THE EFFECTIVENESS OF USING VOCATIONAL-BASED TEACHING MATERIALS FOR SCIENTIFIC WRITING TO IMPROVE ACADEMIC WRITING SKILLS OF POLYTECHNIC STUDENTS - Moh. Thamrin; Achmad Sjaifullah; Umi Anis Ro’isatin (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2018)
This study aims at yielding teaching materials for vocational-based scientific paperwriting that can improve academic writing skills as a focus in Indonesian Languagecourses for Polytechnic students. Particularly, it is aimed at describing the results of (1)evaluation (product test) which consists of expert tests and field tests, and (2) producteffectiveness test. The research method used was a modification of the R2R2development model (recursive, reflective, design, and development and RDR(research, development, research) which resulted in the following stages: a preliminarystudy, selection of design, design development, and product effectiveness test. Reviewgained from the experts and practitioners demonstrated that the teaching material forwriting a scientific paper is in accordance with the characteristics of polytechnicstudents because it emphasizes practical activities. The teaching materials have specialfeatures in terms of presentation. The teaching materials have fulfilled their graphicfeasibility so that their readability is stated very well. The t-test analysis shows that theteaching materials for vocational-based scientific paper writing are effective toimprove the students’ academic writing skills.